I-Witness the best of Jay Taruc - Taruc, Jose Reyes III; Flores, Marissa L. (GMA Network, 2007)
"Panay De Motor" - Jay embarks on a motorcycle trip to document the urban legends of mystical Panay Island. "Maestrang Bulod" - A school in Sorsogon is so remote that teachers cannot go home everyday. They have to eat and sleep inside their classrooms. "Ako At Ang Butanding" - The mysterious arrival of whale sharks in Albay drives Jay into the waters, despite his decades-old fear of the open sea. "Gulong Ng Buhay" - Jay spends days in a wheelchair and discovers that the rights of persons with disabilities are almost completely ignored in Metro Manila. "Kapit Sa Patalim" - Small-time loggers in Quezon are torn between sustaining their natural resources and making a living.